Biomimetic Directional Liquid Transport on a Planar Surface in a Passive and Energy-Free Way - Qing’an Meng; Zhangcan Li; Jie Pang; Kaicheng Yang; Junjie Zhou (Biomimetics)
The development of efficient directional liquid transport systems has become a central focus in numerous research and engineering fields. Natural organisms have evolved intricate structures that facilitate the controlled movement of liquids on planar surfaces. These natural mechanisms offer insights into creating sustainable, energy-efficient technologies that mimic these natural adaptations. The purpose of biomimetic directional liquid transport is to harness the principles found in nature to design systems that can autonomously manage the flow of liquids. One of the core objectives is to achieve efficient liquid directional movement without the need for external energy sources or mechanical pumps. In this article, we review the typical models of natural systems with directional liquid transport on planar surfaces. Next, we reveal the physical mechanism by which surface chemical gradients, wettability gradients, and geometric gradients synergically drive liquid directional motion. Then, we introduce the breakthroughs of bionic surface engineering strategies in water harvesting, directional liquid transport and recent advancements in engineering applications. Finally, we give a conclusion and future perspectives on the development of directional liquid transport.